The Zn(II)-1,4,7-Trimethyl-1,4,7-Triazacyclononane Complex: A Monometallic Catalyst Active in Two Protonation States - Diez-Castellnou, Marta; Salassa, Giovanni; Mancin, Fabrizio; Scrimin, Paolo (Frontiers in Chemistry, 2019)
In this paper, the unusual reactivity of the complex Zn(II)-1,4,7-trimethyl-1,4,7-triazacyclononane (2) in the transesterification of the RNA-model substrate, HPNP (3), is reported. The dependence of the reactivity (k2) with pH does not follow the characteristic bell-shape profile typical of complexes with penta-coordinated metal centers. By the contrary, two reactive species, featuring different deprotonation states, are present, with the tri-aqua complex being more reactive than the mono-hydroxy-diaqua one. Apparently, such a difference arises from the total complex charge which plays an important role in the stability of the transition state/s of the reactions. Relevant insight on the reaction mechanism were hence obtained.